ﺗﻄﺒﻴﻘﺎت دﻟﻴﻞ ’’ﺳﺪ ّ اﻟﺬرﻳﻌﺔ‘‘ ﺎل ’’اﻹﻋﺎﻧﺔ ﻋﻠﻰ ا ﻌﺼﻴﺔ‘‘ ﻓﻘﻪ ا ﻌﺎﻣﻼ تا ﺎﻟﻴﺔ: Application of the Rules of "Sadd al-Dhari'ah" in the Field of "Assisting Sins" in Fiqh of Financial Transactions - Amrulloh, Irsyad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study discusses the rules of Sadd al-Dhari'ah (Closing the Path to Evil) and its influence in preventing assistance for sinful deeds in fiqh of financial transactions. This research begins by defining this rule in language and terms, and explaining its postulates from the Qur'an, hadith, ijma' (agreement of scholars), and reason, then discusses differences of opinion on the principle of its validity, focusing on the position of the Maliki school and their views on this matter. This study also discusses the conditions for the application of the rules of Sadd al Dhari'ah, the most important of which are: the possibility of leading to something haram, the desired goal is indeed haram based on the text, and this rule does not contradict the purpose of sharia or established customs. Furthermore, this study elaborates on the concept of al-'Awanah (aid against sins) and its relation to Sadd al Dhari'ah, emphasizing that the law of a medium depends on the goal to be achieved, and that the law of aid varies depending on how much influence it has and the extent of its damage. The study concludes with the application of fiqh in financial transactions, such as the sale of al-'Aynah (the resale of the same goods), the work used to make alcohol, the receipt of gifts between borrowers and lenders, and the conditions of acceptance in grants. This study shows how the rules of Sadd al-Dhari'ah have contributed to regulating these issues and preventing manipulation of haram things, while maintaining a balance between preventing harm and achieving legitimate interests. Keywords: Sadd al-Dhari'ah, assistance against sins, fiqh of financial transactions, media and purposes, consequences, manipulation of fiqh, madhhab Maliki.